2017
DOI: 10.1017/9781316809747
|View full text |Cite
|
Sign up to set email alerts
|

A History of the Mind and Mental Health in Classical Greek Medical Thought

Abstract: The Hippocratic texts and other contemporary medical sources have often been overlooked in discussions of ancient psychology. They have been considered to be more mechanical and less detailed than poetic and philosophical representations, as well as later medical texts such as those of Galen. This book does justice to these early medical accounts by demonstrating their richness and sophistication, their many connections with other contemporary cultural products and the indebtedness of later medicine to their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 242 publications
0
11
0
Order By: Relevance
“…However, a distinct or systematic psychological methodology for handling mental disease had not yet been advanced, as we can see from the fact that the physiological explanation of mental disorder prompted naturalistic prescriptions for its cure: for example, exercise and diet as part of a daily regime, suitable environment, drugs (e.g., hellebore against melancholy), and, occasionally, invasive methods such as venesection and surgery. It has recently been suggested that the lack of emphasis on the psychosomatic basis of the human being in Classical medicine attests to the collective attempt of Hippocratic doctors to demarcate their professional territory as separate from that of philosophers (Thumiger, 2018).…”
Section: Psychotherapy In the Ancient Worldmentioning
confidence: 99%
“…However, a distinct or systematic psychological methodology for handling mental disease had not yet been advanced, as we can see from the fact that the physiological explanation of mental disorder prompted naturalistic prescriptions for its cure: for example, exercise and diet as part of a daily regime, suitable environment, drugs (e.g., hellebore against melancholy), and, occasionally, invasive methods such as venesection and surgery. It has recently been suggested that the lack of emphasis on the psychosomatic basis of the human being in Classical medicine attests to the collective attempt of Hippocratic doctors to demarcate their professional territory as separate from that of philosophers (Thumiger, 2018).…”
Section: Psychotherapy In the Ancient Worldmentioning
confidence: 99%
“…classical medicine, we do not find anything of this kind. The impression is that the medicine of this early period programmatically excluded from its domain any aspect that might have to do with the emotions, with subjectivity, with the ethical and private – in short, whatever belongs to the personal sphere and comes to the fore in psychotherapy (See: Thumiger, 2017, pp. 335–45).…”
Section: Medicine: the Early Period (Fifth Century Bce)mentioning
confidence: 99%
“…19 On this close and largely social delimitation see Singer (2014), pp. 207–18; Thumiger (2017), pp. 271–2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twentieth-century historiographical concerns about the dangers of an anachronistic reading of the classical texts (Pigeaud, 1981, 1987; Simon, 1972–3, 1978) have generated new scholarship (Ahonen, 2014, 2019; Berrios, 1994; Harris, 2013; Hershkowitz, 1998; Konstan, 2006; Maieron, 2017; Mumford, 1996; Perdicoyianni-Paléologou, 2009a, 2009b; Thiher, 1999; Thumiger, 2017, 2018; Thumiger and Singer, 2018).…”
Section: Introductionmentioning
confidence: 99%